The Bride Wealth of the Ambai Serui Tribe Marriage: A Christian Faith View - Selvie Indriani; Pantjar Simatupang (Global Writing Academica Researching & Publishing, 2023)
A bride wealth is a package of cultural items and money given to the bride and her family by the groom family as a prerequisite for a formal wedding. Bride wealth is practice is ubiquitous, increasingly expensive and creates various marriage related personal and social problems. The objective of this study is to describe the process of determination, material elements, delivery and cultural meanings of bride wealth in the Ambai tribe traditional wedding. The study was conducted using autoethnography methodology supported with in-depth interviews with two emic resource persons, and documentary, photos and videos as secondary sources of data and information. The study shows that in the Ambai tribe tradition, the bride wealth is a prerogative request of the bride nuclear family but it goes through a collective negotiation process that makes it remain reasonable and acceptable to all parties. The bride wealth related processions strengthen the social bonding and the materials reflect indigenous wisdom of the Ambai tribe. Christian education on bride wealth is expected to strengthen the existing culture. Christian education should be able to maintains indigenous culture without in conflict with the principles of the Christian faith.